The replacements - Parker, Jeff, 1966- (Marvel comics (New York, N.Y.), 2008)
"Join the Hulk, Spider-man, Captain America, and the rest of the Avengers in these action-packed crime-fighting adventures for all ages"--P. [4] of cover.